Pengaruh kinerja CSR terhadap biaya utang dengan kualitas audit sebagai variabel moderasi di Indonesia - Anriasa, Lundi; Leon, Farah Margaretha; Purba, Yosephina Endang (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of corporate social responsibility performance on the cost of debt and audit quality as variables that can moderate the relationship between corporate social responsibility performance and the cost of debt. The control variables in this study consisted of firm size, tangbility, ROA, PBV, betarisk, dividends, and NDT. This study adds the leverage control variable as a novelty from previous research. Data collection was conducted using a purposive sampling method sourced from the annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) with certain criteria so that the number of samples in the study was 23 companies. Eviews 10 was used to test the hypothesis using the panel data regression analysis technique. The results of this study indicate that the performance of corporate social responsibility has a significant negative effect on the cost of debt. In addition, audit quality is able to moderate the effect of social responsibility performance on the cost of debt in a significant positive direction. The results of the control variables show that firm size, tangibility, ROA, and betarisk have a significant negative effect on the cost of debt. Meanwhile, the PBV and dividend variables have no effect on debt cost, whereas the NDT and leverage variables have a significant positive effect on debt cost.